Association of Serum Adiponectin and Leptin Levels with Glycemic Control in Type 2 Diabetes Mellitus - Farhan Tariq, Jalal Khan, Mohammad Abid, Tashfeen Ikram Bushra Hussain, Syed Ehsan ullah, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Emerging evidence implicates adiponectin and leptin in glucose homeostasis and metabolicregulation among individuals with type 2 diabetes mellitus (T2DM). The present experimentalstudy investigated their association with glycemic control in a cross-sectional cohort of 120 adult